(untitled) (Analysis in Theory and Applications, 2014)
Let P(z) be a polynomial of degree n, having all its zeros in |z|≤ 1. In this paper, we estimate kth polar derivative of P(z) on |z|=1 and thereby obtain compact generalizations of some known results which among other things yields a refinement of a result due to Paul Turán.